Butterflies and Moths - Morris, Dean. (Milwaukee, 1977)
Discusses the life cycles and behavior patterns of various species of butterflies and moths.
Includes index.
Bibliography: p. 48.
Keywords: Butterflies; Lepidoptera; Juvenile literature; Moths